Primary pancreatic lymphoma and metastatic lymphoma cases diagnosed with ultrasonography guided tru-cut needle biopsy; Two case reports: Pancreatic lymphoma, two case reports - Bağcı, Işıl; Şeker, Nazlı Sena (Journal of Surgery and Medicine, 2023)
Secondary pancreatic involvement can be seen up to 30% of advance staged non-Hodgkin’s lymphoma cases, but primary pancreatic lymphomas constitute only 1% of extranodal lymphomas. Furthermore, 0.2% of the pancreatic space-occupying lesions are primary pancreatic lymphomas, which usually present as a mass in the head of the pancreas with nonspecific symptoms. Therefore, primary pancreatic lymphomas should be considered as differential diagnosis of pancreatic solid lesions. Herein, we report two cases with different clinical presentation and different course of disease resulting in the diagnosis of primary and metastatic pancreatic lymphoma.